1991
DOI: 10.1111/j.1095-8649.1991.tb03142.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of group size on the responsiveness of zebrafish, Brachydanio rerio (Hamilton Buchanan), to alanine, a chemical attractant

Abstract: Previous studies have examined the effects of grouping on the locating (search) phase of foraging and feeding behaviour in fishes. Few studies have examined whether schooling in fishes may facilitate individual foraging by enhancing a group's responsiveness to food odours. The purpose of the current study was to assess the effect of increasing group size on the responsiveness of zebrafish. Eruchydunio rerio (Hamilton Buchanan), to L-alanine, an amino acid which is an important constituent of prey odours for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 36 publications
7
8
0
Order By: Relevance
“…Thus, the collective dynamics create a group-level responsiveness to the environment that is absent at the individual level (19). The resulting increase in gradient-tracking ability for larger groups agrees with previous hypotheses (20,21) and could explain empirical studies showing that grouping facilitates the detection of chemical cues (22)(23)(24) and improves the accuracy of migrations that rely on such cues (25,26).…”
supporting
confidence: 74%
“…Thus, the collective dynamics create a group-level responsiveness to the environment that is absent at the individual level (19). The resulting increase in gradient-tracking ability for larger groups agrees with previous hypotheses (20,21) and could explain empirical studies showing that grouping facilitates the detection of chemical cues (22)(23)(24) and improves the accuracy of migrations that rely on such cues (25,26).…”
supporting
confidence: 74%
“…It has previously been reported that adult zebrafish show a behavioral response to pheromones (Chen and Martinich, 1975;Bloom and Perlmutter, 1977;Van den Hurk et al, 1987;Van der Kraak, 1989;Hall and Suboski, 1995) and to amino acids (Steele et al, 1990(Steele et al, , 1991. Zebrafish clearly respond to alarm pheromone as well as to the amino acids, L-serine, alanine, and cysteine with characteristic attractive or aversive responses, similar to those described in other fishes (von Frisch, 1938(von Frisch, , 1941bHara, 1971Hara, , 1993.…”
Section: Zebrafish Behavioral Responses To Odorantssupporting
confidence: 56%
“…Amino acids strongly attract fishes as food-derived odorants (Steele et al 1990(Steele et al , 1991Koide et al 2009). Zebrafish are capable of discriminating between different amino acids (Miklavc and Valentincic 2012).…”
Section: Amino Acidsmentioning
confidence: 99%